(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Pervious concrete is an advanced, ecological-oriented material, the performance of which is defined by the interactions between porosity, permeability, density and compressive strength. Though higher hydraulic efficiency is achieved but this is counterbalanced by a progressive optimization mix of the matrix with reduction in compressive strength (3-25 MPa) in accordance with increase in porosity. This is a result of reduced interparticle contact and a proportional decrease in density of about 3.5-5% per 1% increase in the void content. A significant 55-65% strength loss (as porosity increases between 20-30%) has been reported, reflecting a less compact internal structure. To obtain a balanced performance it is necessary to optimize mix design, in particular by balancing the water-cement ratio between approximately 0.25-0.30, the appropriate gradation of aggregates, and the incorporating recycled and natural aggregates. Furthermore, the addition of cementitious material and fibers will enhance strong bonding in the microstructure and durability with minimal loss in permeability. Even though pervious concrete has massive potential as a sustainable pavement material, and the beneficial effect on stormwater managing, urban heat-reduction, further development of material engineering and environment friendly construction process is steadily increasing its functional reliability, thus strengthening its contribution to sustainable and climate-resilient urban infrastructure.